KAJIAN BUDAYA DALAM PERSPEKTIF FILOSOFI - Arybowo, Sutamat (Jurnal Masyarakat dan Budaya, 2015)
This paper is part of desk research on the analytical reflection on daily lives. Writer tries to explain the importance of cultural studies from philosophical perspective. The aim of the approach of this writing is to put culture in its proper context, in order to give better recommendation for cultural policy reform. Recent years has witnessed the vast and dynamic development of cultural studies. One of the approaches is by using philosophical perspectives and methods. Differs with other methods, this research tries to prove that scientific truth can be reached through philosophical reasoning, which includes three main components, namely ontology, epistemology and axiology. With this method, culture has found a new meaning as â€œa process of understandingâ€, and no longer it is seen as something that is already â€œgivenâ€. This â€œprocessâ€ is continuously negotiated through the whole social interaction, which depend on the characters of power relation and other relations in the society that changes from time to time.